Pixie: Looking for Meaning and the Third Grade (Analytic Teaching, 1985)
Introduction:  In reviewing my year of Analytic Teaching, several recurring thoughts come to mind.  In this paper, I will attempt to share some beneficial ideas for teachers to use that I feel have been tested sufficiently in a practical setting.  Initially, I felt unsure and clumsy with my group.  By the year's end, the sessions have become very comfortable and therefore probably more productive for all concerned.  Important points that I will explain are: 1. My ground rules, 2. Teacher planning and forethought, 3. Expectations and goals, 4. Topics that interest my children, 5. Rules for the teacher, 6. Use of the manual, 7. My rewards.